Science Board Game Media Based on Team Game Tournament Model to Improve Cognitive Learning Outcomes - Marinda, Annisa Deni; Winarni, Endang Widi; Muktadir, Abdul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The low cognitive learning outcomes of students on the subject of force and the limited availability of interactive learning media are the background of this research. Learning that does not involve students actively causes low motivation and understanding of concepts. This research aims to develop learning media in the form of a Science Board Game based on the Teams Games Tournament (TGT) model to improve the cognitive learning outcomes of fourth-grade elementary school students. The approach used is Research and Development (R&D) with the ADDIE model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques include documentation, observation, questionnaires, validation, and cognitive tests. The trial was conducted on students in grades IV A and IV B. Data analysis was carried out with qualitative data obtained from observations, interviews, and expert validation questionnaires analyzed descriptively qualitatively to evaluate the feasibility of the media and quantitative data regarding students' cognitive learning outcomes were analyzed using descriptive and inferential statistics. The results of the study show that the media that has been developed is in the valid, practical, and effective categories, with an increase in learning outcomes in the medium to high categories. The implication is that game-based media can be an innovative solution to improve the science learning outcomes of elementary school students. The implications of this research show that interactive and competitive learning media innovations can be an effective alternative in increasing student involvement and understanding of science material.